Plasmonic properties of asymmetric dual grating gate plasmonic crystals (Phys. Status Solidi B 4/2016). Issue 4 (April 2016) - Karabiyik, Mustafa; Ahmadivand, Arash; Sinha, Raju; Al‐Amin, Chowdhury; Vabbina, Phani Kiran; Kaya, Serkan; Rupper, Greg; Rudin, Sergey; Shur, Michael; Pala, Nezih
Abstract : Plasmonic THz devices are promising for THz detection, mixing, and generation. In a field effect transistor (FET) structure with 2D electron gas channel capped with periodically spaced grating gates, the metal gates supply the necessary momentum in order to efficiently excite the plasmons by compensating the momentum mismatch between the THz waves in free space and the THz plasmons in the channel. In the study by Karabiyik et al. (pp. 671–675 ), the dispersion relations of asymmetric dual‐grating gate (ADGG) plasmonic FETs are investigated to better understand the excitation and propagation of THz plasmons in them. The analysis shows that the ADGG FETs do not sustain a symmetric charge distribution and their asymmetric charge distribution creates a net dipole moment along the channel resulting in a higher THz response than that of uniform grating gate devices. Moreover, constructive and destructive interference of the plasmons in the asymmetric cavities causes splitting of the energy bands and formation of band gaps known as plasmonic band gap.